Discursive interpersonality: engaging audiences in digital feature articles - Lorés-Sanz, Rosa (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Engaging audiences is widely regarded as essential for science communicators aiming to bridge the gap between the expert knowledge they convey and their target audience's presumed lack of expertise. Drawing on the concept of discursive interpersonality (Suau et al., 2021), this study explores a corpus of 30 digital feature articles from the SciDis Corpus (Pascual and Sancho-Ortiz, 2024) in order to identify and analyse pragmatic strategies and their associated (meta)discursive features used by science communicators to make expert knowledge accessible and engaging for lay audiences. Results show that writers deploy a range of strategies and resources, including not only interactional metadiscourse features, as expected, but also strategic resources adapted from journalistic and narrative discourses. In sum, the study shows that audience-oriented pragmatic strategies (Lorés, 2024b) extend beyond traditional metadiscourse (Hyland, 2005b). Further conclusions point to editorial and disciplinary differences in the use of pragmatic and (meta)discursive engaging strategies.